PENGARUH USIA MENARCHE DAN LAMA MENYUSUI TERHADAP KEJADIAN KANKER PAYUDARA DI RSU DADI KELUARGA PURWOKERTO - Prabandari, Fitria; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Breast cancer is a malignant tumor that attacks breast tissue originating from glandular cells and breast supporting tissues, not including the breast skin. The etiology of breast cancer cannot be explained. However, many studies have shown that there are several factors associated with an increased risk or the possibility of breast cancer. at the Dadi Purwokerto Family General Hospital because of an increase in the incidence of breast cancer from January - October 2014 totaling 2,320 cases of breast cancer. This study uses a restropective case control approach. Data analysis uses non-statistical analysis or referred to as simple statistical analysis. To test the hypothesis about the relationship between two variables used Chi Square. The results of the bivariate analysis will be analyzed using logistic regression on each variable with a value of p <0.25. There is a relationship between menarche age factor and the incidence of breast cancer at Dadi Family Hospital in Purwokerto. There is a relationship between the old factors of breastfeeding and the incidence of breast cancer at Dadi Family Hospital in Purwokerto. Variables that influence breast cancer incidence are age of menarche and duration of breastfeeding. Keywords: Breast Cancer, Age of Menarche, Length of Breastfeeding